Skeleton density and ellipsoid zone loss are prognostic for progression in Macular Telangiectasia Type 2 - Lukas Goerdt; Moritz Berger; Julie Jungblut; Jose Luis Rodriguez Garcia; Kristina Pfau; Philipp Herrmann; Frank G. Holz; Maximilian W. M. Wintergerst (Scientific Reports, 2024)
Abstract Macular Telangiectasia Type 2 (MacTel) is a chronic, progressive disease of the central retina characterized by vascular and neurodegenerative changes. As there is currently no treatment for non-neovascular MacTel, there is a dearth for biomarkers identifying eyes with an increased risk for disease progression for patient counseling and clinical trial recruitment. Eyes were classified to be stable or progressive, defined by the fundus photography-based grading system by Gass and Blodi. First, structural differences between these two groups were assessed, employing optical coherence tomography (OCT) and OCT-angiography. Univariate regression analyses revealed evidence towards a lower superficial retinal layer (SRL) vessel density (VD), skeleton density (SD) and deep retinal layer (DRL) SD in progressing compared to stable eyes (p = 0.05, p = 0.05, p = 0.07). Second, a multivariable predictive model was employed to examine the predictive value of structural and functional parameters for disease progression. Baseline best corrected visual acuity (BCVA) and SRL SD are prognostic for disease progression (p < 0.001, p = 0.05). The presence of ellipsoid zone (EZ) loss is prognostic for future central retinal thickness (p < 0.01). We propose SRL SD, BCVA, and EZ loss as prognostic biomarkers and as possible outcome measures in future interventional studies in MacTel.